Glial remodeling and neuroprotective effects of L-glutamine supplementation on the enteric nervous system in walker-256 tumor-bearing rats - Sara Raquel Garcia de Souza; Juliana Vanessa Colombo Martins Perles; Gleison Daion Piovezana Bossolani; Érika Xavier Santos; Geraldo Emilio Vicentini; Luciane Fracaro; Fernanda Paschoal Blegniski; Flávia Alessandra Guarnier; Emerson Barili; Flávia Cristina Vieira Frez; Camila Caviquioli Sehaber; Mariana Machado Lima; et al. (Tissue and Cell, 2026)

Microencapsulated quercetin and Bifidobacterium animalis attenuate enteric gliosis and mucosal immune activation in the ileum during colorectal carcinogenesis - Sabrina Silva Sestak; João Victor Kuller; Lucas Casagrande; Carla Cristina de Oliveira Bernardo; Lídia Rodrigues Cícero; Fabiana Galvão da Motta Lima; César Agostinho Ferreira; Tania Cristina Alexandrino Becker; Waldiceu Aparecido Verri Junior; Juliana Vanessa Colombo Martins Perles; Jacqueline Nelisis Zanoni (PharmaNutrition, 2026)

Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Loss of tall grass reduces nest survival in Argentinian grasslands - Sofía Martin-Sirito; Stella B. Román; Martin Colombo; Daniel A. Cardoni; Juan P. Isacch (Journal of Ornithology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Exploring preferences and emotional responses of a dairy-based hybrid product: insights from consumer-centric development using different health-oriented clusters - Igor Souza de Brito; Elson Rogério Tavares Filho; Rebeca Barcellos Elhabre de Mattos; Mônica Marques Pagani; Tatiana Colombo Pimentel; Adriano Gomes da Cruz; Eliane Teixeira Mársico; Carolina Pinto de Carvalho Martins; Erick Almeida Esmerino (Food Quality and Preference, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Modelling pesticide concentrations in Japanese paddy fields using the RICEWQ model - Marta Colombo; Julien Boulange; W. Martin Williams; Hirozumi Watanabe (Science of The Total Environment, 2024)

A review of carbon storage in saline aquifers: Mechanisms, prerequisites, and key considerations - Amin Izadpanahi; Martin J. Blunt; Narendra Kumar; Muhammad Ali; Colombo Celso Gaeta Tassinari; Marcio Augusto Sampaio (Fuel, 2024)

Responsible ownership and health education can reduce the time of sporotrichosis treatment in domestic cats - Bianca Moreira de Souza; Salene Angelini Colombo; Roberta do Carmo Teixeira; Isadora Martins Pinto Coelho; Werik dos Santos Barrado; Breno Oliveira Lima Ramos; Érica Lorenza Martins Araujo; Gustavo Canesso Bicalho; Maria Isabel de Azevedo; Kelly Moura Keller; Fabiana Dos Santos Monti; Lorena Diniz Macedo Silva Maia; et al. (Preventive Veterinary Medicine, 2024)

An improved method for determining free amino acids by RP-HPLC/DAD with o-phthalaldehyde derivatization: Method evaluation in beers and wines - Viviane Maria de Sousa Fontes; Tatiana Colombo Pimentel; Ana Beatriz Martins da Silva; Marta Suely Madruga; Marciane Magnani; Marcos dos Santos Lima (Food Chemistry, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

Rhizobacteria control damping-off and promote growth of lima bean with and without co-inoculation with Rhizobium tropici CIAT899 - Linnajara de Vasconcelos Martins Ferreira; Rafael de Almeida Leite; Fernanda de Carvalho; Júlia Fonseca Colombo Andrade; Flávio Henrique Vasconcelos de Medeiros; Fatima Maria de Souza Moreira (Archives of Microbiology, 2023)

Kinetic and mechanistic study of ultrasonic inactivation of Kunitz (KTI) and Bowman-Birk (BBI) inhibitors in relation to process-relevant parameters - Yue Wu; Wu Li; Enrico Colombo; Gregory J.O. Martin; Muthupandian Ashokkumar (Food Chemistry, 2023)

Disjunct resident population of Melodious Lark Mirafra cheniana discovered in East Africa - Brian W. Finch; R. Stratton Hatfield; Silvia Colombo; Adam S. Kennedy; Marije te Raa; Martin Irestedt; Dawid H. de Swardt; Joe Grosel; Derek Engelbrecht; Callan Cohen; Urban Olsson; Paul F. Donald; et al. (Journal of Ornithology, 2023)
We describe the discovery of a previously unknown population of Melodious Lark Mirafra cheniana from northern Tanzania and southern Kenya, some 2000 km north of what was previously thought to be its northern limit in central Zimbabwe. The identification of this population as M. cheniana is based primarily on analyses of mitochondrial DNA and song. We also clarify relationships within this genus by sequencing material of White-tailed Lark Mirafra albicauda for the first time; although its relationships with other species in the group remain unclear, our analyses clearly show it to be different from M. cheniana in the newly discovered population. The discovery of a population of M. cheniana in East Africa conforms to a known pattern for closely related lark species to have disjunct distributions in southern and eastern Africa.

Who let the young‐of‐the‐year ( YOY) up? The pelagic habitat as a nursery and feeding ground area for the YOY Argentine hake Merluccius hubbsi Marini, 1933 - Mauro Belleggia; Gustavo L. Alvarez‐Colombo; Betina A. Santos; Martin Castelletta; Belen Mattera (Journal of Fish Biology, 2022)
The young‐of‐the‐year (YOY) Argentina hake Merluccius hubbsi remained at particular distances off the seabed at pelagic habitat, in a nursery area located in the San Jorge Gulf off south‐western Atlantic. Older specimens were daylight distributed near the bottom in the demersal habitat. In this paper the authors show that the pelagic habitat is favourable for YOY hake compared to the surrounding demersal habitat by decreasing the probability of encounter with larger hake protecting the YOY against conspecific predation, and providing a better food supply. From 303 stomachs of pelagic YOY Argentine hake analysed (60–250 mm), 274 (90.43%) contained prey. Pelagic Argentine YOY hake fed almost exclusively on zooplanktonic crustaceans ( Euphausia spp. and Themisto gaudichaudii ). From 980 demersal specimens (14–82 cm), 572 (58.36%) contained prey, mainly the lobster krill Munida gregaria , followed by other hakes by cannibalism. The intensity of feeding was higher on pelagic layers. The allometric weight–length relationship revealed that the YOY Argentine hake find sufficient food in the pelagic habitat to live and develop, by increasing their relative body thickness. The cannibalism increases from close to zero when the YOY hake are c . 20 m off the seabed, to between 15% (cold season) and 20% (warm season) when they are 10 m off the seabed. These results suggest that the pelagic habitat is a feeding ground for YOY hake, and it is a favourable one compared to the surrounding demersal habitat by protecting the YOY from cannibalism. Pelagic YOY hakes were less abundant and more distant from the bottom during the cold season (14.3 m) than during warm one (11.4 m), probably because of natural mortality and progressive recruitment to demersal habits.

The redundancy effect under morphogenetic and environmental fluctuations. The case of the Dianthus pungens group - Isaura Castro; João Rocha; Maria Martins; Valdemar Carnide; Juan Pedro Martín; Pedro Veiga; Ana Beatriz Serafim; Francisco Amich; Rubén Ramírez-Rodríguez; Giacomo Colombo; António Luis Crespí (Plant Biosystems, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bees and pesticides: the research impact and scientometrics relations - Raiza Abati; Amanda Roberta Sampaio; Rodrigo Mendes Antunes Maciel; Fernanda Caroline Colombo; Gabriela Libardoni; Lucas Battisti; Everton Ricardi Lozano; Nédia de Castilhos Ghisi; Fabiana Martins Costa-Maia; Michele Potrich (Environmental Science and Pollution Research, 2021)

Global Proteomic Profile Integrated to Quantitative and Morphometric Assessment of Enteric Neurons: Investigation of the Mechanisms Involved in the Toxicity Induced by Acute Fluoride Exposure in the Duodenum - Carina Guimaraes de Souza Melo; Jacqueline Nelisis Zanoni; Sara Raquel Garcia de Souza; Isabela Zignani; Aline de Lima Leite; Alessandro Domingues Heubel; Juliana Vanessa Colombo Martins Perles; Marília Afonso Rabelo Buzalaf (Neurotoxicity Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

High export of nitrogen and dissolved organic carbon from an Alpine glacier (Indren Glacier, NW Italian Alps) - Nicola Colombo; Daniele Bocchiola; Maria Martin; Gabriele Confortola; Franco Salerno; Danilo Godone; Michele Eugenio D’Amico; Michele Freppaz (Aquatic Sciences, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Cost-benefit of feeding on anthropogenic organic matter: lipid changes in a detritivorous fish (Prochilodus lineatus) - Eric Demian Speranza; Leandro Martin Tatone; Natalia Cappelletti; Juan Carlos Colombo (Ichthyological Research, 2013)

Depth-dependent abundance of Midas Cichlid fish (Amphilophus spp.) in two Nicaraguan crater lakes - Marie Theres Dittmann; Marius Roesti; Adrian Indermaur; Marco Colombo; Martin Gschwind; Isabel Keller; Robin Kovac; Marta Barluenga; Moritz Muschick; Walter Salzburger (Hydrobiologia, 2012)

Fungemia in cancer patients in Brazil: Predominance of non-albicans species - Marcio Nucci; Maria Isabel Silveira; Nelson Spector; Fernanda Silveira; Eduardo Velasco; Carlos Alberto Martins; Andrea Derossi; Arnaldo L. Colombo; Wolmar Pulcheri (Mycopathologia, 1998)